tRNA abundance, modification and fragmentation in nasopharyngeal swabs as biomarkers for COVID-19 severity - Katanski, Christopher D.; Alshammary, Hala; Watkins, Christopher P.; Huang, Sihao; Gonzales-Reiche, Ana; Sordillo, Emilia Mia; van Bakel, Harm; , Mount Sinai PSP study group; Lolans, Karen; Simon, Viviana; Pan, Tao; Fabre, Shelcie; et al. (Frontiers in Cell and Developmental Biology, 2022)
Emerging and re-emerging respiratory viruses can spread rapidly and cause pandemics as demonstrated by the recent severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) pandemic. The early human immune responses to respiratory viruses are in the nasal cavity and nasopharyngeal regions. Defining biomarkers of disease trajectory at the time of a positive diagnostic test would be an important tool to facilitate decisions such as initiation of antiviral treatment. We hypothesize that nasopharyngeal tRNA profiles could be used to predict Coronavirus Disease 19 (COVID-19) severity. We carried out multiplex small RNA sequencing (MSR-seq) on residual nasopharyngeal swabs to measure simultaneously full-length tRNA abundance, tRNA modifications, and tRNA fragmentation for the human tRNA response to SARS-CoV-2 infection. We identified distinct tRNA signatures associated with mild symptoms versus severe COVID-19 manifestations requiring hospitalization. These results highlight the utility of host tRNA properties as biomarkers for the clinical outcome of SARS-CoV-2.